1985
DOI: 10.1002/jcb.240280402
|View full text |Cite
|
Sign up to set email alerts
|

Actin‐associated cell‐surface glycoprotein from ascites cell microvilli: A disulfide‐linked multimer

Abstract: Isolated microvilli of the MAT-C1 subline of the 13762 rat mammary adenocarcinoma contain a transmembrane complex composed of a cell surface, cytoskeleton-associated glycoprotein (CAG), actin, and a 58,000-dalton polypeptide (58K). The behavior of CAG has been studied by differential centrifugation and velocity sedimentation gradient centrifugation of detergent extracts of microvilli. CAG can be pelleted along with a fraction of the microvillar actin even in the presence of ionic detergents and under microfila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Because anxA5 is a non-membrane-aggregating annexin [50], we speculate that it is involved in the stability of CFTR in the plasma membrane rather than in the trafficking process. Moreover, because anxA5 is involved in the stabilization of the membranes [51], because it binds to the membranes and to actin, because it regulates the function and the distribution of membrane glycoproteins [52] and because CFTR binds to actin [53], we suggest that anxA5 belongs to the three-dimensional network that might stabilize the mutated CFTR at the cell surface increasing its half-life in the plasma membrane. This could explain why the cell surface expression of both Wt-CFTR and ∆F508-CFTR depends on anxA5…”
Section: Discussionmentioning
confidence: 91%
“…Because anxA5 is a non-membrane-aggregating annexin [50], we speculate that it is involved in the stability of CFTR in the plasma membrane rather than in the trafficking process. Moreover, because anxA5 is involved in the stabilization of the membranes [51], because it binds to the membranes and to actin, because it regulates the function and the distribution of membrane glycoproteins [52] and because CFTR binds to actin [53], we suggest that anxA5 belongs to the three-dimensional network that might stabilize the mutated CFTR at the cell surface increasing its half-life in the plasma membrane. This could explain why the cell surface expression of both Wt-CFTR and ∆F508-CFTR depends on anxA5…”
Section: Discussionmentioning
confidence: 91%
“…Our data also support a hypothesis that Sgp 130 is involved in plasma membrane force coupling events but not in junctional-related cell-cell coupling.T hE role of the cytoskeleton in spatially and functionally organizing the cytoplasm of nonerythrocyte cell types has been a subject of broad experimental interest. An important and challenging issue in this area concerns the mechanisms by which cytoskeletal elements, particularly actin microfilaments, assume both specific associations with the plasma membrane and key roles in basic cellular processes (20,22,29,31,42,45,52).Numerous studies have shown actin microfilament-plasma membrane associations to be either (a) highly specialized at discrete attachment sites, such as, for example, the membrane dense plaque of smooth muscle (16,18), the fascia adherens of cardiac muscle (48) or stereocilia of cochlea hair cells (45), or (b) less well-defined structurally and subject to modulation in a series of cellular events that are transient (i.e., cytokinesis) (43) or developmentally regulated (i.e., myofibril attachment to the sarcolemma) (13).Microfilament-plasma membrane associations also appear to be functionally specialized at sites of cell-cell adhesion and at sites of cell contractility where cytoskeletal activities are translated into dynamic cellular events of cytokinesis, endocytosis, and cell movement. We are interested in studying the relative in vivo arrangements of specific membrane proteins as one approach for revealing some of the molecular details that underly functional specializations of microfilament-membrane attachment sites.…”
mentioning
confidence: 99%
“…T hE role of the cytoskeleton in spatially and functionally organizing the cytoplasm of nonerythrocyte cell types has been a subject of broad experimental interest. An important and challenging issue in this area concerns the mechanisms by which cytoskeletal elements, particularly actin microfilaments, assume both specific associations with the plasma membrane and key roles in basic cellular processes (20,22,29,31,42,45,52).…”
mentioning
confidence: 99%